Analysis of the Causes and Countermeasures of Wrongful Conviction Cases in China - Wei Li (Law and Economy, 2023)
After researching and reflecting on the phenomenon of wrongful conviction cases in our country, it is obvious that in recent years all such cases were related to the “contributions” of wrongful conviction cases. We discover too much delay, evasion and resistance from the judicial organs, and their passivity and hesitation make the parties and their families heartbroken, and also make the public heart-breaking. The formation and development of the phenomenon of unjust, false and erroneous cases in China is not the result of one day or one night, but the combined efforts of various subjective and objective reasons. This phenomenon requires sufficient attention and cannot be left in a state of confusion. We should not only explore its superficial causes, but also seek the deep-seated reasons behind it. So we can take appropriate measures to solve this problem from the perspective of judicial reform. While trying to conduct theoretical discussions, we should also propose some feasible solutions and measures.